Study on water-assisted injection molding technology - Ravikumar, Viveganandan (2018)
This report comprises of a detailed presentation and analysis of the internship that is done at Moldetipo. The areas that are described and discussed in detail include, injection molding, various processes used in making a mold, defects in a mold and defects in part . It also analyses the technology of Water Assisted Injection Molding. This report starts by explaining injection molding and injection molding machines, followed by parts of a mold and different process involved in manufacturing a mold. This report also comprises of case study of Water Assisted Injection Molding (WAIM) and the void formation in the parts of WAIM machined. Also, a case study about different parameters that affect the WAIM process.